PENGEMBANGAN SISTEM INFORMASI PENDAPATAN DEALER MOTOR BERBASIS OBJECT ORIENTED - Noerlina, Noerlina (Bina Nusantara University, 2007)
Article explores income system must be design to make easy on the company business process, able tomonitor, and well operation control. Research used analysis and designed method. The analysis result later used todesign a new information system that hoped able to support the company operational activity also solving problemthat occurred from the running system, and able to support the company management in receiving the fast andaccurate information also to give report to help the manager in making decision.Keywords: information system, income, object oriented